Antifungal activity of silver nanoparticles in combination with nystatin and chlorhexidine digluconate against Candida albicans and Candida glabrata biofilms - Monteiro, Douglas R.; Silva, Sónia; Negri, Melyssa; Gorup, Luiz F.; de Camargo, Emerson R.; Oliveira, Rosário; Barbosa, Debora B.; Henriques, Mariana (Wiley, 2013)
Although silver nanoparticles (SN) have been investigated as an alternative to conventional antifungal drugs in the control of Candida-associated denture stomatitis, the antifungal activity of SN in combination with antifungal drugs against Candida biofilms remains unknown. Therefore, the aim of this study was to evaluate the antifungal efficacy of SN in combination with nystatin (NYT) or chlorhexidine digluconate (CHG) against Candida albicans and Candida glabrata biofilms. The drugs alone or combined with SN were applied on mature Candida biofilms (48 h), and after 24 h of treatment their antibiofilm activities were assessed by total biomass quantification (by crystal violet staining) and colony forming units enumeration. The structure of Candida biofilms was analysed by scanning electron microscopy (SEM) images. The data indicated that SN combined with either NYT or CHG demonstrated synergistic antibiofilm activity, and this activity was dependent on the species and on the drug concentrations used. SEM images showed that some drug combinations were able to disrupt Candida biofilms. The results of this study suggest that the combination of SN with NYT or CHG may have clinical implications in the treatment of denture stomatitis. However, further studies are needed before recommending the use of these drugs safely in clinical situations. © 2013 Blackwell Verlag GmbH.
Keywords: Candida biofilms; Chlorhexidine digluconate; Nystatin; Silver nanoparticles; Synergism